Sosialisasi Pentingnya Penentuan Harga Pokok Penjualan dan Pemeriksaan Keuangan Pada Umkm Kelurahan Sidomulyo, Kecamatan Stabat - Nur Aliah; Miftha Rizkina; Atikah Zuhra Sitorus (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to improve the understanding and ability of micro and small business owners in determining the cost of goods sold accurately and conducting basic financial audits to support business sustainability. This activity was carried out in the Sidomulyo sub-district, Stabat district, using socialization and interactive discussion methods. The participants were ten micro and small business owners engaged in various types of businesses. The results of the activity showed that most participants did not have adequate financial records. There was still a lack of accuracy in the use and grouping of accounts. Through this activity, participants gained a good understanding of the importance of determining the cost of goods sold and conducting financial audits as a basis for more measurable and sustainable business management. This activity is expected to encourage micro and small business owners to start implementing simple financial records consistently.